Laudes Rubrics - Measurement and Learning Approach - Foundation, Laudes (Laudes Foundation, 2023)
How can we measure and learn when promoting systems change? It’s a cha llenge that has inspired Laudes Foundation to develop a rubrics-based methodology to help us, our partners and the wider field of philanthro py, understand our contribution to change, while learning and adapting to new and unforeseen circumstances. Change cannot be captured by num bers alone because metrics put the focus on what can be counted, not a lways what’s most important. Rubrics are a framework that set a standa rd for what ‘good’ looks like – and create a shared language for descr ibing and assessing it using both quantitative and qualitative evidenc e. At Laudes Foundation, the rubrics are integrated into our grantmaki ng processes – from the design phase through to measurement, evaluatio n and learning. The four Laudes Foundation rubrics categories Laudes F oundation has developed 21 rubrics that work across different levels, from processes to long-term impact. When measuring a specific initiati ve, a smaller set of relevant rubrics are chosen and assessed on a rat ing scale from ‘harmful’ to ‘thrivable’. The 21 rubrics are categorise d into four groups, with some natural overlap between categories B, C and D. Category A focuses on the process-related aspects of initiative s, including design, implementation, monitoring, communication and lea rning, and organisation and network effectiveness. Category B focuses on the early and later changes that need to happen to create the right conditions to achieve the 2025 outcomes. Category C captures the 2025 outcomes, focusing on how policymakers, financiers, business leaders, and workers and producers behave. Category D captures the 2030 impact s, describing the new reality created as a result of sustained efforts .